O SIMBOLISMO RELIGIOSO EM MIRCEA ELIADE: PASSIVIDADE, DINÂMICA E RESSIGNIFICAÇÃO - Ramalho, Aline Grasiele Araújo (2012)
This research investigates the symbolization process on Mircea Eliade s thought. The study on religious symbolism includes categories of the human as well as concepts and experiences with the sacred lived by the religious men. The world is revealed through symbols, in which it is possible to achieve a better understanding of the human being. This research assistson the understanding of religion as a phenomenonof the culture, whereas the symbolism reveals the mode of human being in the world. This work contemplates the proposal of Eliade s hermeneutics, which refers to a study for the search of meaning and significations in religious documents. Besides the understanding of the hermeneutical method, the possibility of a new epistemology of symbolwas examined. Eliade s propositionon religious symbolism is also explored in the identification of what is considered to be passive and dynamic in the process of religious symbolism, and how this dialectical relation happens. Passivity and dynamic are implicit categories on Eliade sthought,therefore this subject composes an hermeneutic effort to understand the author. The redefinition of religious symbolsis another step that had been observed in the process of symbolization. The redefinition is worked in respect to the experienced sense crisis in the contemporaneity. This is a work that highlights the importance of considering the various disciplines to the comprehension of the religious phenomenon, having a well-establishedphenomenological approach. As this research seeks to interpret the religious data in order toreach the essence or the structure that is present in all religious manifestations, we could say this research grasps both phenomenological and hermeneutical proposition. This study can be characterized by an interpretation of Eliade sthought, where systematization and new possibilities of readings of his worksare presented.